Sensor array spanning multiple radial quadrants to measure body joint movement - Connor, Robert A (2019)
This invention is a sensor array which longitudinally spans a body joint in order to measure movement of that body joint. In an example, this sensor array can comprise four longitudinal sensors which span the body joint in four different radial quadrants, respectively. In an example, this sensor array can comprise six longitudinal sensors which span the body joint in six different radial hextants, respectively. In an example, this sensor array can further comprise a first accelerometer which is proximal to the body joint and a second accelerometer which is distal to the body joint.